Hadits dalam Pendidikan Agama: Fondasi Spritual untuk Pembentukan Karakter Islami - Aldi, Muhammad; Khairanis, Retisfa (INDO PUBLISHING, 2025)
This research aims to explore the role of hadith as a spiritual foundation in religious education and its contribution to Islamic character building. The study focuses on the educational values contained in the hadith and how they can be effectively integrated into the religious education curriculum. Using a qualitative-descriptive approach, the study collected data through literature review, content analysis of the hadith, and in-depth interviews with educators and hadith experts. The results showed that the hadith has broad educational dimensions, including the values of honesty, compassion, responsibility, and tolerance. These values are relevant to build a strong Islamic character in students. The study also found that the integration of hadith in religious education has not been optimal in some institutions due to the lack of comprehensive understanding of the content of hadith and less innovative learning approaches.. The implications of this study include the importance of developing more applicable hadith-based learning modules, training teachers to understand and teach hadith contextually, and collaboration between educational institutions and scholars in developing learning materials. This study makes a significant contribution in strengthening the Islamic spirituality-based educational approach, which is oriented towards the formation of a generation of Muslims who are not only intellectually intelligent, but also have noble character.